THE EFFICACY OF THE ORTILIYA ONE-SIDED EXTRACT IN NORMALIZING THE RECEPTION OF THE ENDOMETRIUM TO ESTROGENS AND PROGESTERONE IN PATIENTS WITH CHRONIC ENDOMETRITIS - Ольга Алексеевна Скоропацкая; Татьяна Александровна Кузнецова; Татьяна Сергеевна Таранина; Татьяна Александровна Болгова (The Publishing House Medicine and Enlightenment, 2017)
The purpose of this study is to assess the impact of treatment with an aqueous extract ortiliya one-sided reception of the endometrium to estrogens and progesterone in female patients with chronic endometritis. The materials and methods. We conducted a prospective study of 20 patients with histologically verified chronic endometritis treated with 2,5 mg per day aqueous extract ortiliya lopsided during two menstrual cycles. Before and after treatment all the patients were carried out clinical and paraclinical examination with assessment of the hormonal reception of the endometrium to estrogens and progesterone and interferon status of the blood. The results and discussion. Improving ultrasound picture of the endometrium on day 21-23 of the cycle identified in all the patients in the form of a reduction in the detection rate of m-echo7 mm less (35 % and 5 %; p < 0,05), hyperechogenic inclusions (100 % and 60 %; p > 0,05) and heterogeneity of the contours of the endometrial (75% and 60%; p>0,05). In the histological picture of chronic endometritis after treatment, decreased the frequency of plasma and leukocyte infiltration (100 % and 20 %; p < 0,05). Also significantly increased the average level of gamma interferon (104,44 ± 6 and 193,55 ± 4  U/ml; p < 0,05), as an indicator of normalization of immunity. The positive dynamics was noted in a significant increase in the average reception level of estrogen in endometrial stromal cells (22,22 ± 2,3 and 44,88 ± 2,6; p < 0,05) and glands (20,22 ± 4,2 and 41 ± 2,2; p < 0,05) and a trend to an increase in the average level of progesterone reception in the endometrial stromal cells (of 32,55 ± 4,3 and 48,77 ± 4,3; p > 0,05) and glands (32,66 ± 2,2 and 48,44 ± 2,2; p > 0,05). Conclusion. Thus, the use of an aqueous extract ortiliya one-sided in patients with chronic endometritis is accompanied by a significant increase in the average reception level of estrogen in the stromal cells (22,22 ± 2,3 and 44,88 ± 2,6; p < 0,05) and endometrial glands (20,22 ± 4,2 and 41 ± 2,2; p < 0,05) against the background of improved ultrasound and histological characteristics of the endometrium.